مقاربات الاحتلال الفرنسي في التعاطي مع الثورة الجزائرية - قندل, جمال (جامعة الوادي - University of Eloued, 2018)
The present study examines the problematic of the position of Algerian women in the revolution of November 1954 in terms of her participation in the manufacture of the revolutionary act of different nature, in a manner that contributed to the advancement and development of the revolution in various and varied fields inside and outside Algéeria, The most important strategic mechanisms that the French occupation has succeeded in are represented in the psychological warfare mechanism adopted in parallel with the development of the revolution, and the reasons for focusing on women as a main party in the form of psychological warfare. In addition of this, the study examines tفhe impact of the psychological war on Algerian women and revolution.
الحرب النفسية الفرنسية و المرأة الجزائرية أنموذجا 1955-1962
مقال
Keywords: Algerian Revolution, Women, Rural, City, French Occupation, Women's Contribution, Psychological Warfare, means of psychological warfare